Privacy trade-offs in international markets - Chisam, Natalie; Moffett, Jordan W.; Germann, Frank; Palmatier, Robert W. (Journal of International Business Studies, 2026)
Abstract Even as data privacy regulations expand globally, their strategic implications for international business remain underexplored. Prior research mostly treats data privacy regulation as a compliance issue, overlooking how firms strategically manage cross-border variations and respond to stakeholder pressures. Drawing on institutional economics and stakeholder theory, this article conceptualizes two trade-offs generated by data privacy regulations: (1) a regulatory, cost–benefit trade-off between privacy compliance costs and customer privacy empowerment and (2) a firm performance, temporal trade-off in which early compliance costs undermine short-term outcomes, before longer-term, trust-based benefits emerge. An international event study of ten regulations across 24 countries affirms that data privacy regulations impose short-term financial setbacks but generate long-term gains. These effects vary across contexts: At regulation, industry, and firm levels, conditions in which internal pressures to minimize risk dominate (intense privacy regulation, strong data dependence, limited resources) intensify early losses. At national levels, environments dominated by external pressures for credible compliance (high formal and informal institutional effectiveness) offset short-term losses and magnify long-term benefits. For international business theory, this study reframes data privacy regulation as a strategic opportunity and highlights how internal versus external legitimacy pressures shape trade-offs that firms must balance to navigate cross-border compliance demands.